A tonoplast Glu/Asp/GABA exchanger that affects tomato fruit amino acid composition. - Snowden, C; Thomas, B; Baxter, C; Smith, J; Sweetlove, L (John Wiley and Sons Ltd, 2015)
Vacuolar accumulation of acidic metabolites is an important aspect of tomato fruit flavour and nutritional quality. The amino acids Asp and Glu accumulate to high concentrations during ripening, while γ-aminobutyrate (GABA) shows an approximately stoichiometric decline. Given that GABA can be catabolised to form Glu and subsequently Asp, and the requirement for the fruit to maintain osmotic homeostasis during ripening, we hypothesised the existence of a tonoplast transporter that exports GABA from the vacuole in exchange for import of either Asp or Glu. We show here that the tomato vacuolar membrane possesses such a transport property: transport of Glu across isolated tonoplast vesicle membranes was trans-stimulated in counterexchange mode by GABA, Glu and Asp. We identified SlCAT9 as a candidate protein for this exchanger using quantitative proteomics of a tonoplast-enriched membrane fraction. Transient expression of a SlCAT9-YFP fusion in tobacco confirmed a tonoplast localisation. The function of the protein was examined by overexpression of SlCAT9 in transgenic tomato plants. Tonoplast vesicles isolated from transgenic plants showed higher rates of Glu and GABA transport than wild-type (WT) only when assayed in counterexchange mode with Glu, Asp, or GABA. Moreover, there were substantial increases in the content of all three cognate amino acids in ripe fruit from the transgenic plants. We conclude that SlCAT9 is a tonoplast Glu/Asp/GABA exchanger that strongly influences the accumulation of these amino acids during fruit development.